Assessing Exchange Rate Competitiveness in the Eastern Caribbean Currency Union - Pineda, Emilio (IMF Working Papers; Working Paper ;, 2009)
This paper uses three methods to assess movements of real exchange rates in the ECCU over time. First, the purchasing power parity hypothesis is tested and then used to provide a benchmark for equilibrium real exchange rates in the region. Second, a fundamentals-based equilibrium real exchange rate approach is used to explore sources of real exchange rate fluctuations in ECCU countries. And third, a macroeconomic balance approach is used to estimate equilibrium current account or current account "norms". The main finding of these analyses is that there is little evidence of overvaluation of the EC dollar. Furthermore, this paper contributes to the literature by analyzing the distinctive impact of tourism in determining real exchange rates through the wealth effect induced by tourism-driven increases in terms of trade and productivity.